2007
DOI: 10.1007/s10773-007-9625-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Game of Two Discriminable Coins

Abstract: In some recent letters, it was reported that quantum strategies are more successful than classical ones for coin-tossing and roulette game. In this paper, we will solve the quantum game of two discriminable coins. And we develop two methods, analogy method and isolation method, to study this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Wang et al [7] also generalized the coin tossing game to an n-state game. Ren et al [8] developed specific methods that enabled them to solve the problem of quantum coin-tossing in a roulette game. Specifically, they used two methods, which they called analogy and isolation methods respectively, to tackle the above problem.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al [7] also generalized the coin tossing game to an n-state game. Ren et al [8] developed specific methods that enabled them to solve the problem of quantum coin-tossing in a roulette game. Specifically, they used two methods, which they called analogy and isolation methods respectively, to tackle the above problem.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, their axes of symmetry intersect in an angle π 8 , as shown in Figure 4. Moreover, their product FH, which is given in (3), is just the rotator R 2π 8 , as can be verified by employing Formula (7). Therefore, by invoking the presentation (6), associating s to F, and t to H, or vice versa, it becomes evident that F and H generate the dihedral group D 8 .…”
Section: The Connection Between Pqg and D 8 31 Matrix Representations Of Rotations And Reflectionsmentioning
confidence: 76%
“…Afterwards, many researchers generalized this game to n-dimensional quantum systems. Important results in this direction were obtained by [6][7][8]. These results indicated that under a specific set of rules, the quantum player does have an advantage over the classical player.…”
Section: Related Workmentioning
confidence: 95%
“…Afterwards, many researchers generalized this game to n-dimensional quantum systems. Important results in this direction were obtained by [6], [7], and [8]. These results indicated that under a specific set of rules, the quantum player does have an advantage over the classical player.…”
Section: Related Workmentioning
confidence: 91%